Break‐and‐Build Strategy for the Synthesis of 2‐Benzoylbenzoxazoles from o‐Aminophenols and Acetophenones. Issue 8 (4th March 2021) - Nguyen, Le Anh; Ngo, Quoc Anh; Retailleau, Pascal; Nguyen, Thanh Binh
Abstract: Although compounds with a 2‐benzoylbenzoxazole motif are biologically relevant, there are only a few methods for synthesizing them, most of which relied on multistep process or required substrates bearing activating groups. Herein, we report an efficient method for the synthesis of such compounds by direct reactions of o ‐aminophenols with acetophenones promoted by sulfur in DMSO. The reaction was found to proceed via a Willgerodt rearrangement‐type benzoxazolation of acetophenones followed by a benzylic oxidation to reinstall the carbonyl function. This method has a broad substrate scope and good tolerance for sensitive functional groups. Abstract :